(untitled) (Journal of Nepal Geological Society, 2020)
The quality of spring water in the Higher Himalaya of Helambu area, Sindhupalchok district, Central Nepal was carried out. A total of fifty seven springs were surveyed to study different physical and chemical parameters, i.e. electric conductivity (EC), total dissolved solids (TDS), potential of hydrogen (pH), dissolved oxygen (DO) and temperature. Among them, six springs were tested for chemical parameters. The results show that the distribution of EC and TDS is greater towards the lower elevation i.e. southern part near the settlement and agricultural land with the value ranging from 13 – 219 µS/cm and 7.08 – 161 mg/l respectively. The distribution of pH is inconsistent with the elevation and ranges from 2.27 – 6.66 throughout the area. The distribution of DO is greater at the central region and towards the lower elevation with the value ranging from 2.77 – 6.33 mg/l. The temperature ranges from 12.4 – 22.8 oC and increases with a decrease in the elevation. All the physiochemical parameters, except for pH, lies within the permissible range given by National Drinking Water Quality Standards (NDWQS, 2005) and World Health Organization (WHO) (2004) standards. The Water Quality Index (WQI) shows that overall area has excellent to good water quality in terms of drinkability, agricultural and industrial purposes. However, increasing urbanization might degrade the quality in future so proper and sustainable management strategies must be adopted to protect and preserve these groundwater resources.